2020
DOI: 10.1093/gerona/glaa090
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Supplementation Improves Cognitive Function and Mood with Changes in Gut Microbiota in Community-Dwelling Older Adults: A Randomized, Double-Blind, Placebo-Controlled, Multicenter Trial

Abstract: Probiotics have been proposed to ameliorate cognitive impairment and depressive disorder via the gut–brain axis in patients and experimental animal models. However, the beneficial role of probiotics in brain functions of healthy older adults remains unclear. Therefore, a randomized, double-blind, and placebo-controlled multicenter trial was conducted to determine the effects of probiotics on cognition and mood in community-dwelling older adults. Sixty-three healthy elders (≥65 years) consumed either placebo or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
237
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(245 citation statements)
references
References 44 publications
5
237
1
2
Order By: Relevance
“…The suggestion that changes in the diet could affect BDNF via modulating microbiota composition is appealing and is supported by several studies that have shown a link between microbiota composition, BDNF concentrations [84], and cognition [85]. This link can also be seen in the respective studies from Haghighat et al [54] and Kim et al [57] where the microbiota populations changed upon supplementation. In this context, it is significant that the studies in the probiotics sub-cluster showed no significant changes in BDNF concentrations [51,53].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The suggestion that changes in the diet could affect BDNF via modulating microbiota composition is appealing and is supported by several studies that have shown a link between microbiota composition, BDNF concentrations [84], and cognition [85]. This link can also be seen in the respective studies from Haghighat et al [54] and Kim et al [57] where the microbiota populations changed upon supplementation. In this context, it is significant that the studies in the probiotics sub-cluster showed no significant changes in BDNF concentrations [51,53].…”
Section: Discussionmentioning
confidence: 89%
“…Probiotic supplementation with different doses of Lactobacillus helveticus IDCC3801-fermented milk showed no overall effect on plasma BDNF concentrations in apparently healthy subjects [56]. Finally, probiotic supplementation with Bifidobacterium bifidum BGN4 and Bifidobacterium longum BORI in apparently healthy subjects did result in a significant increase in serum BDNF concentrations [57], but supplementation with Lactobacillus helveticus and Bifidobacterium longum in subjects with depressive symptoms did not [58].…”
Section: Probioticsmentioning
confidence: 90%
“…Thus, the efficacy of prebiotics to modify gut microbiota composition in the elderly could be related to frailty, but their effects on inflammation were very modest despite the long intervention period. Regarding probiotics, a mix of two Bifidobacterium species in an over 65 years old South Korean population, achieved a gradual and significant reduction of Allisonela , Eubacterium , Clostridiales order and Prevotellaceae family after 12 weeks [ 86 ]. The reduction of Prevotellaceae abundance is in contrast with the dynamics of this taxa under other treatments as exercise or MD where this genus shows the opposite trend.…”
Section: Gut Microbiota Targeted Interventions In the Elderlymentioning
confidence: 99%
“…Probiotic supplementation attenuated HPA-axis response to stress and protected mice from a stress-induced decrease in hippocampal neurogenesis (Ait-Belgnaoui et al, 2014). Single or mixed probiotic supplementation positively affected cognitive function in healthy adults (Allen et al, 2016; Steenbergen et al, 2015), the elderly (Chung et al, 2014; Kim et al, 2020) and patients with depression (Rudzki et al, 2019), AD (Akbari et al, 2016), HIV-1 and fibromyalgia (Roman et al, 2018). However, most of these studies included cognitive performance as a primary outcome but did not analyze changes in GMB composition.…”
Section: Gut Microbiome Modification For Improved Cognition: Diet Prmentioning
confidence: 99%